EFEKTIVITAS PENGGUNAAN MEDIA BERBASIS WORDWALL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI 32 BANDA ACEH - Maulidar, Maulidar; Mislinawati, Mislinawati; Vitoria, Linda (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The phenomenon in the field shows that the learning process is not effective because students often feel bored and do not follow Pancasila education lessons. Wordwall-based media is one type of media that can be used to produce effective learning. The method in this research is a qualitative approach with descriptive research type. The research subjects were 34 class IV students at SD Negeri 32 Banda Aceh. The instruments used include student learning activity observation sheets, test sheets, and questionnaires to measure student responses. The research results showed that: 1) students' learning activities reached 89.2% with the criteria